Tissue-specific inactivation of HAT cofactor TRRAP reveals its essential role in B cells - Leduc, Claire (Landes Bioscience, 2014)
The transformation/transcription domain-associated protein (TRRAP) is a common component of many histone acetyltransferase (HAT) complexes. Targeted-deletion of the Trrap gene led to early embryonic lethality and revealed a critical function of TRRAP in cell proliferation. Here, we investigate the function of TRRAP in murine B cells. To this end, we ablated Trrap gene in a B cell-restricted manner and studied its impact on B-cell development and proliferation, a pre-requisite for class switch recombination (CSR), the process that allows IgM-expressing B lymphocytes to switch to the expression of IgG, IgE, or IgA isotypes. We show that TRRAP deficiency impairs B-cell development but does not directly affect CSR. Instead, cells induced to proliferate undergo apoptosis. Our findings demonstrate a central and general role of TRRAP in cell proliferation.